Effect of crystal orientation of GaN/V2O5 core-shell nanowires on piezoelectric nanogenerators. (June 2019) - Waseem, Aadil; Johar, Muhammad Ali; Hassan, Mostafa Afifi; Bagal, Indrajit V.; Ha, Jun-Seok; Lee, June Key; Ryu, Sang-Wan
Abstract: GaN/V2 O5 core-shell nanowire (NW) piezoelectric generators of controlled crystallographic orientations were fabricated, and the device performance was characterized. Catalyst-assisted c- and m-axis GaN NWs were grown on a c-plane GaN thin film by varying the NH3 flow rate and reactor pressure. The grown NWs were then utilized to fabricate the flexible piezoelectric nanogenerators (PNGs) to practically investigate the impact of the c- and m-axis GaN NWs on the piezoelectric response. The c-axis GaN NWs exhibited a higher piezoelectric output than m-axis GaN NWs. Furthermore, the GaN/V2 O5 core-shell structure was utilized in the NWs to suppress the internal carrier screening that degrades the piezoelectric output. The maximum output voltage (27 V) exhibited by core-shell c-axis NWs was thrice the voltage exhibited by pristine c-axis GaN NWs (9 V). A stability test was performed for one hour to verify the feasibility of using flexible PNGs for real applications. The high stability of PNGs was attributed to the flexibility and high crystallinity of the NWs. Graphical abstract: GaN/V2 O5 core-shell nanowire (NW) piezoelectric generators of controlled crystallographic orientations are reported. Catalyst-assisted c- and m-axis GaN NWs grown by MOCVD are utilized to fabricate the flexible piezoelectric nanogenerators to investigate the impact of the c- and m-axis GaN NWs on the piezoelectric response. The c-axis GaN NWs exhibited the higher piezoelectric output than m-axis GaN NWs. The GaN/V2 O5 core-shell structure is utilized in the NWs which further enhanced the output voltage to 27 V and output current to 590 nA.Image 1 Highlights: C- & m-axis GaN NWs are grown by MOCVD for piezoelectric generators. The piezoelectric output for pristine c-axis NWs is twice the output of m-axis NWs. The piezoelectric output of the GaN/V2 O5 core-shell NWs is three times of pristine NWs. PNGs exhibited long-term stability due to excellent mechanical properties of NWs. GaN/V2 O5 heterojunction suppressed the junction current screening effect.